Retrograde Tibial Nailing: a minimally invasive and biomechanically superior alternative to angle-stable plate osteosynthesis in distal tibia fractures - Kuhn, Sebastian (BioMed Central, 2014)
BACKGROUND: Currently, antegrade intramedullary nailing and minimally invasive plate osteosynthesis (MIPO) represent the main surgical alternatives in distal tibial fractures. However, neither choice is optimal for all bony and soft tissue injuries. The Retrograde Tibial Nail (RTN) is a small-caliber prototype implant, which is introduced through a 2-cm-long incision at the tip of the medial malleolus with stab incisions sufficient for interlocking. During this project, we investigated the feasibility of retrograde tibial nailing in a cadaver model and conducted biomechanical testing. METHODS: Anatomical implantations of the RTN were carried out in AO/OTA 43 A1-3 fracture types in three cadaveric lower limbs. Biomechanical testing was conducted in an AO/OTA 43 A3 fracture model for extra-axial compression, torsion, and destructive extra-axial compression. Sixteen composite tibiae were used to compare the RTN against an angle-stable plate osteosynthesis (Medial Distal Tibial Plate, Synthes(®)). Statistical analysis was performed by Student's t test. RESULTS: Retrograde intramedullary nailing is feasible in simple fracture types by closed manual reduction and percutaneous reduction forceps, while in highly comminuted fractures, the use of a large distractor can aid the reduction. Biomechanical testing shows a statistically superior stability (p < 0.001) of the RTN during non-destructive axial loading and torsion. Destructive extra-axial compression testing resulted in failure of all plate constructs, while all RTN specimens survived the maximal load of 1,200 N. CONCLUSIONS: The prototype retrograde tibial nail meets the requirements of maximum soft tissue protection by a minimally invasive surgical approach with the ability of secure fracture fixation by multiple locking options. Retrograde tibial nailing with the RTN is a promising concept in the treatment of distal tibia fractures.